Bacteriostatic activity and partial characterization of the bacteriocin produced by L. plantarum sp. isolated from traditional sourdough - Mina Zangeneh (Food Science & Nutrition, 2020)
Abstract This study was aimed to isolate and partially characterizes the bacteriocin produced by an L. plantarum sp. isolated from traditional sourdough. The bacteriocin was partially purified, and after treating it with different harsh conditions, its antibacterial activity was evaluated against L. monocytogenes as an indicator. Also, the growth phase during which the bacteriocin is produced, and its mode of action, was examined. Finally, the molecular weight of this compound was evaluated by using SDS‐PAGE analysis. According to the results, this bacteriocin had a molecular weight well lower than 10 kDa that was mainly produced at the early stationary phase and reached its highest activity (3,200 AU/ml) at the same stage. It was tolerant toward a wide range of pH (2–10), temperatures (−20 to 120°C), and high concentrations of NaCl. Notably, the bacteriocin‐producing strain had proteolytic activity, while the bacteriocin produced by that showed resistance to proteolytic enzymes (pepsin, trypsin, and proteinase K). Also, it was revealed that the bacteriocin activity is mostly bacteriostatic so that it considerably inhibits pathogens’ growth, particularly S. aureus, E. coli, and L. monocytogenes. These characteristics prove that strain and its bacteriocin can be considered as one of the most promising agents to use in the food industry.